Improved neurodevelopmental prognostication in isolated corpus callosal agenesis: fetal magnetic resonance imaging‐based scoring system. (1st July 2021) - Diogo, M. C.; Glatter, S.; Prayer, D.; Gruber, G. M.; Bettelheim, D.; Weber, M.; Dovjak, G.; Seidl, R.; Kasprian, G.
ABSTRACT: Objectives: Corpus callosal agenesis (CCA) is one of the most common brain malformations and is generally associated with a good outcome when isolated. However, up to 25% of patients are at risk of neurodevelopmental delay, which currently available clinical and imaging parameters are inadequate to predict. The objectives of this study were to apply and validate a fetal magnetic resonance imaging (MRI) anatomical scoring system in a cohort of fetuses with isolated CCA and to evaluate the correlation with postnatal neurodevelopmental outcome. Methods: This was a retrospective cohort study of cases of prenatally diagnosed isolated CCA (as determined on ultrasound and MRI), with normal karyotype and with known postnatal neurodevelopmental outcome assessed by standardized testing. A fetal brain MRI anatomical scoring system based on seven categories (gyration, opercularization, temporal lobe symmetry, lamination, hippocampal position, basal ganglia and ventricular size) was developed and applied to the cohort; a total score of 0–11 points could be given, with a score of 0 representing normal anatomy. Images were scored independently by two neuroradiologists blinded to the outcome. For the purpose of assessing the correlation between fetal MRI score and neurodevelopmental outcome, neurodevelopmental test results were scored as follows: 0, 'below average' (poor outcome); 1, 'average'; and 2, 'above average' (good outcome). Spearman's rank coefficient was used to assess correlation, and inter‐rater agreement in the assessment of fetal MRI score was calculated. Results: Twenty‐one children (nine females (42.9%)) fulfilled the inclusion criteria. Thirty‐seven fetal MRI examinations were evaluated. Mean gestational age was 28.3 ± 4.7 weeks (range, 20–38 weeks). All fetuses were delivered after 35 weeks' gestation with no perinatal complications. Fetal MRI scores ranged from 0 to 6 points, with a median of 3 points. Inter‐rater agreement in fetal MRI score assessment was excellent (intraclass correlation coefficient, 0.959 (95% CI, 0.921–0.979)). Neurodevelopmental evaluation was performed on average at 2.6 ± 1.46 years (range, 0.5–5.8 years). There was a significant negative correlation between fetal MRI score and neurodevelopmental outcome score in the three areas tested: cognitive (ρ = –0.559, P  < 0.0001); motor (ρ = –0.414, P  = 0.012) and language (ρ = –0.565, P  < 0.0001) skills. Using fetal MRI score cut‐offs of ≤ 3 (good outcome) and ≥ 4 points (high risk for poor outcome), the correct prognosis could be determined in 20/21 (95.2% (95% CI, 77.3–99.2%)) cases. Conclusion: By assessing structural features of the fetal brain on MRI, it may be possible to better stratify prenatally the risk of poor neurodevelopmental outcome in CCA patients. © 2020 Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology. Abstract : Linked article: There is a comment on this article by Carbillon and Amarenco. Click here to view the Correspondence.